2012
DOI: 10.1103/physrevb.86.104109
|View full text |Cite
|
Sign up to set email alerts
|

Pressure-induced amorphization of methane hydrate

Abstract: Pressure-induced amorphization of methane hydrate has been investigated by molecular dynamics simulation. In accord with experimental results of Tulk et al., a crystalline → amorphous transition was confirmed at 3.3 GPa where the water lattice collapsed around the encaged methane. Thermal annealing at 5.5 GPa allows the water to adopt a lower energy conformation with a denser structure. In both structures, methane molecules are immobilized and maintain long-range correlation as in the crystal. Consequently, bo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
13
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 27 publications
1
13
0
Order By: Relevance
“…A similar hindrance of rotational motion of molecular guests was found in MD simulations of PIA of CS-II THF hydrate 17 and CS-I CH 4 hydrate. 25 Actual PIA implies the “collapse” of D cages. 24 Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…A similar hindrance of rotational motion of molecular guests was found in MD simulations of PIA of CS-II THF hydrate 17 and CS-I CH 4 hydrate. 25 Actual PIA implies the “collapse” of D cages. 24 Fig.…”
Section: Resultsmentioning
confidence: 99%
“…PIA is initiated by the deformation of the 6-membered rings of the large H cages. 17,24,25 When approaching PIA, the translational motion of Ar atoms inside the cages decreased drastically. A similar hindrance of rotational motion of molecular guests was found in MD simulations of PIA of CS-II THF hydrate 17 and CS-I CH 4 hydrate.…”
Section: Three Amorphous Forms Of Ar Hydratesmentioning
confidence: 99%
See 1 more Smart Citation
“…Both potential are proven in terms of reasonable thermodynamics for ice, e.g., with accurate melting points of ∼270 K. , Naturally, TIP4P-Ice is expected to be more accurate (at the very least kinetically), , due to explicit long-range dipolar and Coulombic electrostatic interactions, particularly at solid–liquid interfaces . Indeed, one interesting matter concerns a detailed comparison of mW versus TIP4P-Ice in terms of sudden pressurization-response behavior, as regards characterization of (probably metastable intermediates’) structural, energetic and dynamical properties, as well as their likelihood of reversibility within nanoseconds to ice I h , given that refs , found that for both pressure-amorphised ice and methane hydrate, removal of pressure led to recovery of a defective, near-crystalline state, i.e., the transformations were near-reversible. We performed MD for ∼70–130 ns at 240 K (owing to be a near-optimal temperature for potential interesting propagation of ice-stacking faults, if present), under pressures of up 30 kbar, on systems ranging in size from ∼40,000 to 1 million molecules for TIP4P-Ice and at the latter size for mW (given greater computational speed).…”
mentioning
confidence: 99%
“…Certainly, the strong tetrahedral biasing in mW appears to be reinforced by the smaller interplanar spacing (e.g., 3.79 versus 4.15 Å at 10 kbar, cf. Figure ) under higher-pressure conditions, with the three-body nature of the Stillinger–Weber potential not capturing the atomistic realism of explicit Bernal–Fowler (ice-rule) hydrogen bonds under severe compaction, and the tendency for these to collapse into the amorphous , or liquid state. Indeed, at elevated pressures, nuclear quantal effects become all the more important in high-pressure ices (whether crystalline or amorphous), or condensed aqueous phases in general; French and Redmer have taken great care in developing a thermodynamic potential for high-pressure ices, while Sugimura et al have highlighted the delicate intricacies of hydrogen-bond symmetrization in high-pressure ice polymorphs and Ikeda has very recently shown that path-integral simulation is needed to define pressure more accurately for high-pressure-ice dynamics .…”
mentioning
confidence: 99%